Ideological Intrusion in Ahmadiyya Qur’anic Exegesis - Siti Khodijah; Musyarrofah (Waraqat: Jurnal Ilmu-Ilmu Keislaman, 2025)
Ahmadiyya Qur’anic exegesis presents a distinctive hermeneutical framework that diverges significantly from mainstream Islamic interpretations, particularly in relation to ideological intrusions (al-dakhi>l) embedded in its exegetical narratives. This study critically investigates the patterns of ideological intrusion in the exegesis of both the Qadiani and Lahori branches, using a qualitative textual analysis. Primary sources include Haqiqat al-Wahy and Tadhkirah by Mirza Ghulam Ahmad, along with exegetical works by Maulawi Sher Ali, Malik Ghulam Farid, and Muhammad Ali. Anchored in the classical theory of al-dakhi>l fi> al-tafsi>r and informed by critical hermeneutics, the analysis identifies three dominant patterns of ideological intrusion: allegorical reinterpretations of miracles, historical reconstruction of the figure of Prophet Isa a.s., and the redefinition of khatam al-nabiyyi>n. While the Qadiani faction tends to affirm Ghulam Ahmad’s prophethood explicitly, the Lahori branch emphasizes rationalism and the role of mujaddidism. The study concludes that Ahmadiyya exegetical methodology, marked by a synthesis of modern rationalism, spiritual subjectivity, and historical reinterpretation, reveals a persistent tension between interpretive innovation and commitment to traditional principles such as sanad and ijma>‘. These findings offer a significant contribution to contemporary Islamic hermeneutics.